Preparation, biological evaluation and QSAR analysis of urea substituted 2, 4-diamino-pyrimidine anti-malarials. Issue 12 (20th October 2022) - Toviwek, Borvornwat; Riley, Jennifer; Mutter, Nicole; Anderson, Mark; Webster, Lauren; Hallyburton, Irene; Gleeson, Duangkamol; Read, Kevin D.; Gleeson, M. Paul
Abstract : Twenty six new phenylurea substituted 2, 4-diamino-pyrimidines active against Plasmodium falciparum ( Pf ) 3D7 are reported. Abstract : The synthesis and evaluation of twenty six new phenylurea substituted 2, 4-diamino-pyrimidines against Plasmodium falciparum ( Pf ) 3D7 are reported. Compounds were prepared to improve both anti-malarial activity and selectivity of the series previously reported by our group. Additional properties have been determined to assess their potential as anti-malarial leads including; HepG2 cytotoxicity, solubility, permeability, and lipophilicity, as well as in vitro stability in human and rat microsomes. We also assess their inhibition profile against a diverse set of 10 human kinases. Molecular docking, cheminformatics and bioinformatics analyses were also undertaken. Compounds 40 demonstrated the best anti-malarial activity at Pf 3D7 (0.09 μM), good selectivity with respect to mammalian cytotoxicity (SI = 54) and low microsomal clearance. Quantitative structure activity relationship (QSAR) analyses point to lipophilicity being a key driver of improved anti-malarial activity. The most active compounds in the series suffered from high lipophilicity, poor aqueous solubility and low permeability. The results provide useful information to guide further chemistry iterations.